Solving nondeterministic polynomial complete problems optically and the design of its light source - Zheng, Mengying. (2013)
This thesis contains two parts. The first part presents the design and performance of a soliton mode-locked fiber laser. While the second half discusses and validate the proposed optical way in solving Nondeterministic Polynomial (NP) -complete problem. The optimized mode-locked laser is a preferable optical source to be utilized in solving NP-complete problem.